Management of primary iliopsoas abscess in an immunocompetent patient followed by streptococcal toxic shock syndrome: A case report. (23rd March 2015) - Hirooka, Nobutaka; Edo, Naoki; Danbara, Hisanori; Nishimura, Hiroki; Obuchi, Yasuhiro; Tanaka, Yuji
Objectives: Clinical diagnosis of iliopsoas abscess can be challenging, as this pathology often presents without obvious focal findings. Iliopsoas abscess should thus be a differential diagnosis for patients presenting with fever of unknown origin. Patient and methods: A 62-year-old healthy Japanese man showed primary iliopsoas abscess of Klebsiella pneumoniae complicated by shock after a complete course of treatment for streptococcal toxic shock syndrome. Successful treatment was achieved with culture-driven antibiotic selection and delayed drainage. Results: This case demonstrates the importance of identifying the causative microorganisms in iliopsoas abscess to guide therapy. The standard treatments for iliopsoas abscess are antibiotics and drainage of the abscess. Management of this case included successful antibiotic use along with delayed drainage. Conclusion: This case report advances the knowledge on the etiology of iliopsoas abscess and sheds light on the need for scientific development of a treatment strategy.